Molecular Chaperone GRP94/GP96 in Cancers: Oncogenesis and Therapeutic Target - Duan, Xiaofeng; Iwanowycz, Stephen; Ngoi, Soo; Hill, Megan; Zhao, Qiang; Liu, Bei (Frontiers in Oncology, 2021)
During tumor development and progression, intrinsic and extrinsic factors trigger endoplasmic reticulum (ER) stress and unfolded protein response, resulting in the increased expression of molecular chaperones to cope with the stress and maintain tumor cell survival. Heat shock protein (HSP) grp94, also known as gp96, is an ER paralog of HSP90 and has been shown to promote survival signaling during tumor-induced stress and modulate the immune response through its multiple clients including TLRs, integrins, LRP6, GARP, IGF, and HER2. Clinically, elevated expression of grp94 correlates with an aggressive phenotype and poor clinical outcome in a variety of cancers. Thus, grp94 is a potential molecular marker and therapeutic target in malignancies. In this review, we will undergo deep molecular profiling of grp94 in tumor development as well as summarize the individual roles of grp94 in common cancers including breast cancer, colon cancer, lung cancer, liver cancer, multiple myeloma, and others. Finally, we will briefly review the therapeutic potential of selectively targeting grp94 for the treatment of cancers.